The N-Town play : drama and liturgy in medieval East Anglia - Granger, Penny (Westfield medieval studies, 2009)
The dramatic text known as the N-Town Play, from fifteenth-century East Anglia, is a significant but mysterious compilation of late-medieval vernacular theatre. It differs radically from the better-known Northern medieval mystery plays in that it offers a.